Resin composition and power module

By using a composition of bisphenol skeleton content multifunctional epoxy resin and a trihydroxyphenyl methane type epoxy resin in the packaging material of the semiconductor work mold, and combining it with a high content inorganic filler, the problem of difficult to guarantee the reliability of the semiconductor work mold contact point in a high temperature environment is solved, and the reliability and adhesion of the packaging material are achieved.

JP7654973B2Active Publication Date: 2025-04-02SUMITOMO BAKELITE CO LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
JP2020212247
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2020-12-22
Publication Date
2025-04-02
Estimated Expiration
2040-12-22

AI Technical Summary

Technical Problem

The prior art is difficult to ensure the contact point reliability of semiconductor work modes in high temperature environments, especially due to the development of SiC and GaN equipment, the operating temperature and thermal stress increase, and traditional packaging materials are difficult to meet the reliability requirements in high temperature environments.

Method used

An epoxy resin composition comprising a bisphenol skeleton content multifunctional epoxy resin or trihydroxyphenyl methane type epoxy resin and is prepared with 82% to 90% inorganic filler, the glass transition temperature is between 170°C and 300°C and a linear expansion coefficient between 5 ppm/K and 15 ppm/K and 25 ppm/K to 65 ppm/K to ensure the reliability of the packaging material under high temperature environments.

Benefits of technology

By using this resin composition, the reliability of the semiconductor work mode in a high temperature environment can be significantly improved, module deformation can be reduced, and adhesion between the packaging material and the heat sink and the junction layer can be improved, thereby improving the reliability of the overall work mode.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007654973000002
    Figure 0007654973000002
  • Figure 0007654973000001
    Figure 0007654973000001
Patent Text Reader

Abstract

To provide a resin-sealed type power module which can secure high reliability even in a high temperature region, and a resin composition used as a resin-sealing material of the power module.SOLUTION: A resin composition contains an epoxy resin and an inorganic filler and is used to seal a power module 10 that has a metal circuit board 3, a power semiconductor element 1 provided on one surface of the metal circuit board, a joint layer 2 that joins the power semiconductor element and the metal circuit board and is composed of a sintering paste, and a heat dissipation sheet 4 laminated on a surface opposite to a surface provided with the power semiconductor element of the metal circuit board, in which a glass transition temperature of the resin composition is 170°C or higher and 300°C or lower, an average coefficient α1 of linear expansion at a temperature equal to or higher than the glass transition temperature of the cured product of the resin composition is 5 ppm / K or more and 15 ppm / K or less, and an average coefficient α2 of linear expansion at a temperature equal to or lower than the glass transition temperature is 25 ppm / K or more and 65 ppm / K or less.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a resin composition and a power module. More specifically, the present invention relates to a resin composition for use as a sealing material for a power module, and a power module produced using the same. [Background technology]

[0002] In semiconductor power modules that incorporate power semiconductor elements such as IGBTs, power MOSFETs, and diodes, materials with high thermal conductivity and electrical insulation are generally used for the insulating plates because the power semiconductor elements generate a large amount of heat. In medium to large capacity semiconductor power modules that generate a large amount of heat, ceramics with high thermal conductivity are mainly used for the insulating plates. Such semiconductor modules are required to achieve both cost reduction and maintaining and improving reliability.

[0003] As a technique for improving the reliability of resin sealing of semiconductor devices that operate at high temperatures, for example, Patent Document 1 describes a semiconductor power module obtained by sealing with epoxy resin a structure including a ceramic insulating substrate, a first electrode disposed on one side of the ceramic insulating substrate, a Si semiconductor chip bonded to the electrode via solder, a second electrode disposed on one side of the ceramic insulating substrate, and a lead bonded to the second electrode via solder. Patent Document 1 describes that the linear expansion coefficient of the epoxy resin used as a sealant is adjusted to be close to both the linear expansion coefficient of the solder and the linear expansion coefficient of the ceramic insulating substrate, thereby suppressing warping of the module after soldering and improving the reliability of the soldered connection. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] JP 2006-179732 A Summary of the Invention [Problem to be solved by the invention]

[0005] However, in recent years, in the field of power semiconductors, the development of SiC elements and GaN elements has led to an increasing demand for operation at higher temperatures than before. As the operating temperature of a power semiconductor device increases, the thermal stress generated at the joint also increases, and the structure disclosed in Patent Document 1 sometimes fails to ensure sufficient reliability of the joint.

[0006] The present invention has been made in consideration of the above problems, and an object of the present invention is to provide a resin-sealed power module that is capable of ensuring high reliability even in high temperature ranges, and a resin composition for use as a resin sealing material for such a power module. [Means for solving the problem]

[0007] According to the present invention, A metal circuit board; a power semiconductor element provided on one surface of the metal circuit board; a bonding layer made of a sintering paste that bonds the power semiconductor element and the metal circuit board; a heat dissipation sheet laminated on a surface of the metal circuit board opposite to a surface on which the power semiconductor element is provided, A resin composition used to seal the power semiconductor element, the bonding layer, the circuit board, and the heat dissipation sheet, The resin composition includes an epoxy resin and an inorganic filler, the epoxy resin is a biphenyl skeleton-containing polyfunctional epoxy resin or a tris(hydroxyphenyl)methane type epoxy resin having an epoxy equivalent of 90 to 300; The inorganic filler is present in an amount of 82% by mass or more and 90% by mass or less based on the total solid content of the resin composition, The glass transition temperature of the resin composition is 170° C. or higher and 300° C. or lower, Glass transition temperature of the cured product of the resin composition less than The average linear expansion coefficient α1 at is 5 ppm / K or more and 15 ppm / K or less, and the glass transition temperature EndThe resin composition has an average linear expansion coefficient α2 of 25 ppm / K or more and 65 ppm / K or less.

[0008] Further, according to the present invention, A metal circuit board; a power semiconductor element provided on one surface of the metal circuit board; a bonding layer made of a sintering paste that bonds the power semiconductor element and the metal circuit board; a heat dissipation sheet laminated on a surface of the metal circuit board opposite to a surface on which the power semiconductor element is provided, a sealing material that covers the power semiconductor element, the bonding layer, the circuit board, and the heat dissipation sheet, The sealing material is made of a cured product of the resin composition. A power module is provided. Effect of the Invention

[0009] According to the present invention, there are provided a resin-sealed power module capable of ensuring high reliability even in high temperature ranges, and a resin composition for use as a resin sealing material for such a power module. [Brief description of the drawings]

[0010] [Figure 1] 1 is a cross-sectional view showing a schematic diagram of a power module according to an embodiment of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0011] Hereinafter, embodiments of the present invention will be described with reference to the drawings. In all the drawings, the same components are denoted by the same reference numerals, and the description thereof will be omitted as appropriate.

[0012] <Power Module 10> A power module 10 according to the present embodiment will be described. FIG. 1 is a cross-sectional view that shows a schematic diagram of the power module 10 according to the embodiment of the present invention. In the following, for ease of explanation, the positional relationship (upper / lower relationship, etc.) of each component of the power module 10 may be described as being as shown in each drawing. However, the positional relationship in this explanation is unrelated to the positional relationship during use or manufacture of the power module 10.

[0013] 1, the power module 10 of this embodiment is a laminated structure including a Cu circuit 3 as a metal circuit board and a power semiconductor chip 1 as a power semiconductor element provided on one surface of the Cu circuit 3 via a sintering layer 2 made of sintering paste, which is joined to a Cu base plate (heat dissipation member) 5 via a heat dissipation sheet 4. In the power module 10, the power semiconductor chip 1 is electrically connected by a lead frame 6. In the power module 10, the Cu base plate 5, the heat dissipation sheet 4, the Cu circuit 3, the sintering layer 2, the power semiconductor chip 1, and the lead frame 6 are sealed with a sealing material 7.

[0014] <Power semiconductor chip 1> The power semiconductor chip 1 is, for example, an insulated gate bipolar transistor (IGBT) and a diode, etc. An electrode pattern (not shown) is formed on the upper surface of the power semiconductor chip 1, and a conductive pattern (not shown) is formed on the lower surface of the power semiconductor chip 1. The lower surface of the power semiconductor chip 1 is bonded to one surface of the Cu circuit 3 via a sintering layer 2, which is a bonding layer. The electrode pattern on the upper surface of the power semiconductor chip 1 is electrically connected to a lead frame .

[0015] The power semiconductor chip 1 is a semiconductor made of, for example, SiC, GaN, Ga2O3, or diamond. The power consumption of the power semiconductor chip 1 is, for example, 2.0 W or more, preferably 3.0 W or more, and may be, for example, 4.0 W or less. The voltage of the power semiconductor chip 1 is, for example, 1.0 V or higher, preferably 3.0 V or higher, and may be, for example, 5.0 V or higher. Also, the voltage of the power semiconductor chip 1 may be, for example, 100 V or lower. Also, the power density of the power semiconductor chip 1 is, for example, 10 W / cm 3 or higher, preferably 20 W / cm 3 or higher, and may be, for example, 30 W / cm 3 or higher. Also, the power density of the power semiconductor chip 1 may be, for example, 200 W / cm 3 or lower. Also, the power semiconductor chip 1 can operate at a temperature higher than that of a conventional Si semiconductor, for example, in a high-temperature environment of 200 °C or higher.

[0016] <Sintering layer 2> The sintering layer 2 is a bonding layer formed by sintering a sintering paste containing metal particles. As the sintering paste, any one of an Ag sintering paste containing silver particles, an Al sintering paste containing aluminum particles, and a Cu sintering paste containing copper particles can be used.

[0017] The above-described sintering paste is provided between the power semiconductor chip 1 and the Cu circuit 3 and laminated, and the power semiconductor chip 1 and the Cu circuit 3 are joined by the sintering layer 2 through a sintering process. The Cu circuit 3 and the lead frame 7 are joined by the sintering layer 2. In the sintering layer 2, a sintering network (metal bonding bus) of metal particles is formed, realizing high thermal conductivity and low electrical resistance. From the viewpoint of improving the bonding property by the sintering layer 2, the Cu circuit 3 and the lead frame 7 may be subjected to surface treatment of plating with the metal contained in the sintering paste. Specifically, in this embodiment, the surfaces of the Cu circuit 3 and the lead frame 7 may be subjected to Ag plating.

[0018] <Cu circuit 3> The Cu circuit 3 is a metal circuit board made of a conductive metal material. A power semiconductor chip 1 is provided on a circuit pattern formed on one surface (the upper surface in the figure) of the Cu circuit 3 via a sintering layer 2, which is a bonding layer.

[0019] The Cu circuit 3 is a circuit board patterned with thick copper (rolled copper), and has a thickness of, for example, 0.3 mm to 5 mm. For example, thick copper (rolled copper) can be suitably used as the metal material constituting the Cu circuit 3. This makes the Cu circuit 3 have a relatively small resistance value. At least a part of the Cu circuit 3 may be covered with a solder resist layer.

[0020] The Cu circuit 3 is formed, for example, by processing a metal layer (such as thick copper) laminated on the upper surface of the base 5A of the Cu base plate 5 via a heat dissipation sheet 4 into a predetermined pattern by cutting and etching it, or it is attached to the Cu circuit 3 with the heat dissipation sheet 4 in a state where it has already been processed into a predetermined pattern.

[0021] The lower limit of the thickness of the Cu circuit 3 is, for example, 0.3 mm or more. If it is equal to or greater than this value, heat generation in the circuit pattern can be suppressed even in applications requiring high current. The upper limit of the thickness of the circuit pattern 20 is, for example, 5.0 mm or less, preferably 4.0 mm or less, and more preferably 3.0 mm or less. If it is equal to or less than this value, circuit processability can be improved, and the substrate as a whole can be made thinner.

[0022] <Heat dissipation sheet 4> The heat dissipation sheet 4 is disposed between the Cu circuit 3 and the Cu base plate 5. The heat from the power semiconductor chip 1 is received by the Cu circuit 3, and is then transferred to the Cu base plate 5, which is heat dissipation means, via the heat dissipation sheet 4. This allows the heat generated from the power semiconductor chip 1, which is a heat generating body, to be effectively dissipated to the outside of the power module 10 while maintaining the insulation of the power module 10. This makes it possible to improve the insulation reliability of the power module 10.

[0023] The planar shape of the heat dissipation sheet 4 is not particularly limited and can be appropriately selected according to the shapes of the Cu circuit 3 and the Cu base plate 5, and can be, for example, rectangular. The film thickness of the heat dissipation sheet 4 is, for example, 50 μm or more and 250 μm or less. This allows the heat of the Cu circuit 3 to be more effectively transferred to the Cu base plate 5 while improving the mechanical strength and heat resistance. Furthermore, the heat dissipation sheet 4 has an excellent balance between heat dissipation and insulation. The thermal conductivity of the heat dissipation sheet 4 is not particularly limited, but is preferably 10 W / mK (175° C.) or more, more preferably 15 W / mK (175° C.) or more.

[0024] [Material of heat dissipation sheet 4] The heat dissipation sheet 4 is, for example, a resin sheet, and is formed using a resin composition for sheets. The resin composition for sheets will be described below. In this embodiment, the resin composition for the sheet preferably contains a thermosetting resin (A), a filler (B), and a curing agent (C), etc. When the resin composition contains a thermosetting resin, the heat dissipation insulation sheet is a B-staged version of the thermosetting resin (A).

[0025] [Thermosetting resin (A)] Examples of the thermosetting resin (A) used as the material of the heat dissipation sheet 4 include epoxy resin, cyanate resin, polyimide resin, benzoxazine resin, unsaturated polyester resin, phenol resin, melamine resin, silicone resin, bismaleimide resin, phenoxy resin, and acrylic resin. As the thermosetting resin (A), one of these may be used alone, or two or more may be used in combination. Among these, from the viewpoint of high insulating properties, the thermosetting resin (A) is preferably an epoxy resin, a phenol resin, or a phenoxy resin.

[0026] Examples of epoxy resins include bisphenol type epoxy resins such as bisphenol A type epoxy resin, bisphenol F type epoxy resin, bisphenol E type epoxy resin, bisphenol S type epoxy resin, bisphenol M type epoxy resin (4,4'-(1,3-phenylenediisopridiene) bisphenol type epoxy resin), bisphenol P type epoxy resin (4,4'-(1,4-phenylenediisopridiene) bisphenol type epoxy resin), and bisphenol Z type epoxy resin (4,4'-cyclohexydiene bisphenol type epoxy resin); phenol novolac type epoxy resin, cresol novolac type epoxy resin, trisphenol group methane type novolac type epoxy resin, tetraphenol group ethene type epoxy resin, and the like. Examples of the epoxy resins include novolac-type epoxy resins such as aryl alkylene-type epoxy resins, novolac-type epoxy resins having a condensed ring aromatic hydrocarbon structure, biphenyl-type epoxy resins, aryl alkylene-type epoxy resins such as xylylene-type epoxy resins and biphenyl aralkyl-type epoxy resins, naphthylene ether-type epoxy resins, naphthol-type epoxy resins, naphthalene diol-type epoxy resins, bifunctional to tetrafunctional epoxy-type naphthalene resins, binaphthyl-type epoxy resins, and naphthalene aralkyl-type epoxy resins, anthracene-type epoxy resins, phenoxy-type epoxy resins, dicyclopentadiene-type epoxy resins, norbornene-type epoxy resins, adamantane-type epoxy resins, and fluorene-type epoxy resins. One of these may be used alone, or two or more may be used in combination.

[0027] Among the epoxy resins, from the viewpoint of further improving heat resistance and insulation reliability, it is preferable to use one or more types selected from the group consisting of bisphenol type epoxy resins, novolac type epoxy resins, biphenyl type epoxy resins, aryl alkylene type epoxy resins, naphthalene type epoxy resins, anthracene type epoxy resins, and dicyclopentadiene type epoxy resins.

[0028] Examples of the phenol resin include novolac-type phenol resins such as phenol novolac resin, cresol novolac resin, and bisphenol A novolac resin, and resol-type phenol resins, etc. One of these may be used alone, or two or more of them may be used in combination. Among the phenolic resins, phenolic novolac resins are preferred.

[0029] The content of the thermosetting resin (A) is preferably 1% by mass or more, more preferably 5% by mass or more, based on the total amount of the sheet resin composition, while the content is preferably 30% by mass or less, more preferably 20% by mass or less, based on the total amount of the sheet resin composition. When the content of the thermosetting resin (A) is at least the above lower limit, the handleability of the sheet resin composition is improved, the heat dissipation insulation sheet can be easily formed, and the strength of the heat dissipation insulation sheet is improved. When the content of the thermosetting resin (A) is not more than the above upper limit, the linear expansion coefficient and elastic modulus of the heat dissipation insulation sheet are further improved, and the thermal conductivity is further improved.

[0030] [Filler (B)] The filler (B) is used from the viewpoints of improving the thermal conductivity of the heat dissipation sheet 4 and obtaining strength.

[0031] The filler (B) used as the material of the heat dissipation sheet 4 is preferably a thermally conductive filler. More specifically, from the viewpoint of achieving a balance between thermal conductivity and electrical insulation, examples of the filler (B) include silica, alumina, boron nitride, aluminum nitride, and silicon carbide. These may be used alone or in combination of two or more. Of these, the filler (B) is preferably alumina or boron nitride.

[0032] The content of the filler (B) is preferably 90% by mass or less, more preferably 80% by mass or less, based on the total amount of the sheet resin composition, while from the viewpoint of thermal conductivity, the content is preferably 40% by mass or more, more preferably 50% by mass or more, based on the total amount of the sheet resin composition.

[0033] [Hardening agent (C)] When the sheet resin composition used as the material for the heat dissipation sheet 4 uses an epoxy resin or a phenol resin as the thermosetting resin (A), it preferably further contains a curing agent (C).

[0034] As the curing agent (C) used as a material of the heat dissipation sheet 4, one or more types selected from the curing catalyst (C-1) and the phenol-based curing agent (C-2) can be used. Examples of the curing catalyst (C-1) include organic metal salts such as zinc naphthenate, cobalt naphthenate, tin octylate, cobalt octylate, bisacetylacetonate cobalt (II), and trisacetylacetonate cobalt (III); tertiary amines such as triethylamine, tributylamine, and 1,4-diazabicyclo[2.2.2]octane; imidazoles such as 2-phenyl-4-methylimidazole, 2-ethyl-4-methylimidazole, 2,4-diethylimidazole, 2-phenyl-4-methyl-5-hydroxyimidazole, and 2-phenyl-4,5-dihydroxymethylimidazole; triphenylphosphine, tri-p-tolylphosphine, tetraphenylphosphonium tetraphenylborate, triphenylphosphine triphenylborane, and 1,2-bis-(diphenylphosphine)-2-phenylphosphine; Examples of the curing catalyst (C-1) include organic phosphorus compounds such as phenol, bisphenol A, nonylphenol, and other phenolic compounds; organic acids such as acetic acid, benzoic acid, salicylic acid, p-toluenesulfonic acid, and other organic acids, or mixtures thereof. As the curing catalyst (C-1), one of these, including its derivatives, can be used alone, or two or more of these, including its derivatives, can be used in combination. The content of the curing catalyst (C-1) is not particularly limited, but is preferably from 0.001% by mass to 1% by mass based on the total amount of the resin composition for a sheet.

[0035] Examples of the phenol-based curing agent (C-2) include novolac-type phenolic resins such as phenol novolac resin, cresol novolac resin, trisphenolmethane-type novolac resin, naphthol novolac resin, and aminotriazine novolac resin; modified phenolic resins such as terpene-modified phenolic resin and dicyclopentadiene-modified phenolic resin; aralkyl-type resins such as phenol aralkyl resins having a phenylene skeleton and / or biphenylene skeleton and naphthol aralkyl resins having a phenylene skeleton and / or biphenylene skeleton; bisphenol compounds such as bisphenol A and bisphenol F; and resol-type phenolic resins, and these may be used alone or in combination of two or more. Among these, from the viewpoints of increasing the glass transition temperature and decreasing the linear expansion coefficient, the phenol-based curing agent (C-2) is preferably a novolac-type phenol resin or a resol-type phenol resin.

[0036] The content of the phenol-based curing agent (C-2) is not particularly limited, but is preferably 1% by mass or more, more preferably 5% by mass or more, based on the total amount of the sheet resin composition. On the other hand, the content is preferably 30% by mass or less, more preferably 15% by mass or less, based on the total amount of the sheet resin composition.

[0037] [Coupling agent] The sheet resin composition used as the material for the heat dissipation sheet 4 may contain a coupling agent. The coupling agent can improve the wettability at the interface between the thermosetting resin (A) and the filler (B).

[0038] The coupling agent used as the material for the heat dissipation sheet 4 is not particularly limited, but it is preferable to use, for example, one or more coupling agents selected from an epoxy silane coupling agent, a cationic silane coupling agent, an amino silane coupling agent, a titanate-based coupling agent, and a silicone oil-type coupling agent. The content of the coupling agent is not particularly limited, but is preferably 0.05% by mass or more, more preferably 0.1% by mass or more, based on 100% by mass of the filler (B), while the content is preferably 3% by mass or less, more preferably 2% by mass or less, based on 100% by mass of the filler (B).

[0039] [Phenoxy resin (E)] The sheet resin composition used as the material for the heat dissipation sheet 4 may contain a phenoxy resin (E). By containing the phenoxy resin (E), the bending resistance of the heat dissipation insulation sheet can be improved. Furthermore, by including the phenoxy resin (E), it is possible to reduce the elastic modulus of the heat dissipation insulation sheet, and to improve the stress relaxation ability of the heat dissipation insulation sheet.

[0040] Furthermore, when the phenoxy resin (E) is contained, the viscosity increases, which reduces the flowability and suppresses the generation of voids. Furthermore, when the heat dissipation insulation sheet is used in close contact with a metal member, the adhesion between the metal and the cured product of the sheet resin composition can be improved. These synergistic effects can further increase the insulation reliability of the obtained power module.

[0041] Examples of the phenoxy resin (E) used as the material of the heat dissipation sheet 4 include phenoxy resins having a bisphenol skeleton, phenoxy resins having a naphthalene skeleton, phenoxy resins having an anthracene skeleton, and phenoxy resins having a biphenyl skeleton, etc. Phenoxy resins having a structure having a plurality of these skeletons can also be used.

[0042] The content of the phenoxy resin (E) is preferably, for example, 3% by mass or more and 10% by mass or less with respect to the total amount of the sheet resin composition.

[0043] [Other ingredients] The sheet resin composition used as the material for the heat dissipation sheet 4 may further contain an antioxidant, a leveling agent, etc., within the scope of not impairing the effects of the present invention.

[0044] <Cuベースプレート5> The Cu base plate 5 is a type of heat dissipation member, and has a copper plate-shaped base 5A and a plurality of fins 5B extending integrally from the lower surface of the base 5A. As the heat dissipation member, for example, an aluminum base plate may be adopted in addition to the Cu base plate 5. Furthermore, as long as it has a function of acquiring heat generated by the power semiconductor chip 1 via the Cu circuit 3 and dissipating it elsewhere, it is not limited to a general heat dissipation member and may be a part of another configuration (for example, a housing) or the like.

[0045] <Lead frame 7> The lead frame 7 supports and fixes the power semiconductor chip 1 and also electrically connects it to external wiring, and is a member made by pressing, etching, or the like, a thin plate of a metal material such as copper or iron.

[0046] <Sealing material 6> The sealing material 6 is, for example, a molding resin, and integrally seals the power semiconductor chip 1, the sintering layer 2, the Cu circuit 3, the heat dissipation sheet 4, the Cu base plate 5, and the lead frame 7 inside.

[0047] In this sealing, a part of the lead frame 7 is sealed, and the other part that is not sealed is connected to an external device. As for the Cu base plate 5, the upper surface and side surface of the base portion 5A of the Cu base plate 5 are covered and sealed with the sealing material 6. The lower surface and the fin portion 5B of the Cu base plate 5 are not covered with the sealing material 6. That is, the sealing material 6 covers and seals the power semiconductor chip 1 so as to cover a part or all of the side surface in the thickness direction of the base portion 5A of the Cu base plate 5. Here, a configuration in which all of the side surfaces of the base portion 5A of the Cu base plate 5 are covered with the sealing material 6 is illustrated.

[0048] The encapsulant 6 is composed of a cured product of the encapsulant resin composition of the present embodiment. The cured product of the encapsulant resin composition of the present embodiment constituting the encapsulant 6 has a glass transition temperature of 170° C. or more and 300° C. or less. less than The average linear expansion coefficient α1 at is 5 ppm / K or more and 15 ppm / K or less, and the glass transition temperature End The average linear expansion coefficient α2 at 25 ppm / K or more and 65 ppm / K or less is thereby made to be approximately the same as the thermal expansion coefficients of the encapsulating material 6, and thus even when the power module is used in a high-temperature environment, warping is reduced and a high level of adhesion between the heat dissipation sheet 4 and the sintering layer 2 is achieved. As a result, the reliability of the obtained power module can be improved. Here, the average linear expansion coefficient α1 of the heat dissipation sheet 4 (glass transition temperature less than ) is about 10 to 15 ppm / K, and the average linear expansion coefficient α2 of the heat dissipation sheet 4 (glass transition temperature End ) is about 20 to 25 ppm / K. The average linear expansion coefficient α of the sintering layer 2 is about 20 to 25 ppm / K. The cured product of the encapsulating resin composition of this embodiment has a linear expansion coefficient close to both the heat dissipation sheet 4 and the sintering layer 2, and therefore has excellent adhesion to them. The linear expansion coefficient of the encapsulating resin composition can be controlled by adjusting the materials used in the resin composition and the amounts of the materials mixed.

[0049] In one embodiment, the glass transition temperature of the cured product of the encapsulating resin composition of the present embodiment less than The average linear expansion coefficient α1 in the above ranges preferably from 8 to 15 ppm / K, and more preferably from 9 to 14 ppm / K. End The average linear expansion coefficient α2 in is preferably 25 to 60 ppm / K, and more preferably 25 to 55 ppm / K. The encapsulating resin composition having a linear expansion coefficient in the above range has excellent adhesion to the heat dissipation sheet 4 and the sintering layer 2.

[0050] [Components of sealing material 6 (mold resin)] The molding resin of the encapsulant 6 is a cured product of the thermosetting resin composition of this embodiment (sometimes referred to as the "resin composition" in this specification) that contains an epoxy resin (A) and an inorganic filler (B). The components contained in the thermosetting resin composition for the encapsulant will be described in detail below.

[0051] [Epoxy resin (A)] Examples of the epoxy resin (A) used in the resin composition of this embodiment include crystalline epoxy resins such as bisphenol type epoxy resins, such as bisphenol A type epoxy resins, bisphenol F type epoxy resins, and tetramethylbisphenol F type epoxy resins, biphenyl type epoxy resins, stilbene type epoxy resins (OCN), and hydroquinone type epoxy resins; novolac type epoxy resins such as cresol novolac type epoxy resins, phenol novolac type epoxy resins, and naphthol novolac type epoxy resins; phenylene skeleton-containing phenol aralkyl type epoxy resins, biphenylene skeleton-containing phenol aralkyl type epoxy resins, phenylene skeleton-containing naphthol aralkyl type epoxy resins, and alkoxynaphthalene skeleton-containing phenol aralkyl type epoxy resins. Examples of the epoxy resins include phenol aralkyl epoxy resins such as aralkyl epoxy resins; naphthylene ether epoxy resins, naphthol epoxy resins, naphthalene diol epoxy resins, bifunctional to tetrafunctional epoxy naphthalene resins, binaphthyl epoxy resins, and naphthalene aralkyl epoxy resins; trifunctional epoxy resins such as triphenol methane epoxy resins (MF) and alkyl-modified triphenol methane epoxy resins; modified phenol epoxy resins such as dicyclopentadiene-modified phenol epoxy resins and terpene-modified phenol epoxy resins; and heterocyclic epoxy resins such as triazine nucleus-containing epoxy resins. These may be used alone or in combination of two or more. Among them, it is preferable to use cresol novolac epoxy resins (OCN), triphenol methane epoxy resins (MF), biphenyl skeleton-containing polyfunctional epoxy resins (polyvalent MAR), and binaphthalene epoxy resins (naphthalene resins) that exhibit high Tg because they do not impair the reliability of the semiconductor chip even when the semiconductor chip is heated to high temperatures.

[0052] The epoxy equivalent of the epoxy resin is preferably 90 to 300. If the epoxy equivalent is too small, the reactivity with the curing agent tends to decrease. If the epoxy equivalent is too large, the mechanical strength of the cured product of the resin composition tends to decrease.

[0053] The content of the epoxy resin (A) is not particularly limited, but is preferably 2% by mass or more, more preferably 4% by mass or more, based on the total amount of the resin composition. When the lower limit of the blending ratio is within the above range, there is little risk of causing a decrease in fluidity in the sealing process. In addition, the upper limit of the blending ratio of the entire resin composition is also not particularly limited, but is preferably 22% by mass or less, more preferably 20% by mass or less, based on the total amount of the resin composition. When the upper limit of the blending ratio is within the above range, the linear expansion coefficient and elastic modulus of the sealing material can be adjusted to an appropriate range. As a result, even if a temperature change occurs during the operation of the power module, peeling from the surrounding members (such as chips and heat dissipation sheets) can be suppressed, and the reliability of the power module as a whole can be improved.

[0054] The ICI viscosity of the epoxy resin (A) at 150°C is preferably set appropriately depending on the content of the inorganic filler (B), and for example, the upper limit is preferably 60 poise or less, more preferably 50 poise or less, and further preferably 40 poise or less. This improves the fluidity of the encapsulant resin composition and makes it easier to realize low-temperature encapsulation. On the other hand, the lower limit of the ICI viscosity of the epoxy resin (A) at 150°C is not particularly limited, and may be, for example, 0.01 poise or more. Note that 1 poise is 0.1 Pa·s.

[0055] [Inorganic filler (B)] Examples of the inorganic filler (B) used in the resin composition of this embodiment include silica, alumina, kaolin, talc, clay, mica, rock wool, wollastonite, glass powder, glass flakes, glass beads, glass fiber, silicon carbide, silicon nitride, aluminum nitride, carbon black, graphite, titanium dioxide, calcium carbonate, calcium sulfate, barium carbonate, magnesium carbonate, magnesium sulfate, barium sulfate, cellulose, aramid, and wood, etc. These may be used alone or in combination of two or more.

[0056] The content of the inorganic filler in the resin composition of the present embodiment is preferably 80% by mass or more, more preferably 82% by mass or more, and even more preferably 83% by mass or more, based on the total solid content of the resin composition, from the viewpoint of obtaining a desired linear expansion coefficient. Also, from the viewpoint of more effectively improving the flowability and filling property during molding of the encapsulating resin composition, the content of the inorganic filler is preferably 90% by mass or less, more preferably 88% by mass or less, and even more preferably 86% by mass or less, based on the total solid content of the resin composition.

[0057] The average particle size of the inorganic filler (B) is not particularly limited, but is typically 1 to 100 μm, preferably 1 to 50 μm, and more preferably 1 to 20 μm. An appropriate average particle size can improve the filling ability around the semiconductor element in the mold cavity. The volumetric particle size distribution of the inorganic filler (B) can be measured by a commercially available laser type particle size distribution analyzer (for example, SALD-7000, manufactured by Shimadzu Corporation).

[0058] In a preferred embodiment, the inorganic filler (B) contains silica powder. Examples of silica powder include crystalline silica (fractured crystalline silica), fused silica (fractured amorphous silica, spherical amorphous silica), and liquid sealing silica (spherical amorphous sealing silica for liquid sealing materials). Among them, fused spherical silica is preferred from the viewpoint of easily achieving low-temperature and low-pressure sealing.

[0059] In another preferred embodiment, the inorganic filler (B) contains an alumina powder. The alumina powder has an α-crystallization rate of 50% or more, preferably 55% or more, and more preferably 60% or more. The upper limit of the α-crystallization rate is, for example, 80% or less, preferably 75% or less. By using an alumina powder having an α-crystallization rate of the above lower limit or more, a resin composition having high thermal conductivity can be obtained. In addition, by using an alumina powder having an α-crystallization rate of the above upper limit or less, the manufacturing cost of the alumina powder can be reduced, and as a result, the manufacturing cost of the resin composition and the final product can be reduced.

[0060] Here, the α-crystallization rate can be calculated by X-ray diffraction measurement, which can be performed using, for example, a JDX-3500 type X-ray diffraction device (manufactured by JEOL Ltd.) and the following method.

[0061] (Method for measuring α-phase content) X-ray diffraction measurements were performed on powders made by mixing α-phase alumina powder AA-05 (manufactured by Sumitomo Chemical Co., Ltd.) and θ-phase alumina powder Taimicron TM-100D (manufactured by Taimei Chemical Co., Ltd.) in weight ratios of 0:10, 5:5, and 10:0, and the integrated intensity of the α-phase peak detected near 2θ = 43° was calculated, and a calibration curve of the mixing ratio and integrated intensity was created. Next, X-ray diffraction measurements were performed on the sample alumina powder, the integrated intensity of the peak near 2θ = 43° was calculated, and the α-phase content (α-crystallization rate) was obtained from the calibration curve created above.

[0062] The alumina powder used in the resin composition of the present embodiment preferably has a spherical shape, which allows the alumina powder to be blended in a high loading amount.

[0063] The alumina powder used in this embodiment may be alumina powder obtained by a flame fusion method using electrofused alumina pulverized material obtained by the Bayer process as raw material powder. The flame fusion method is a method in which such raw material powder is sprayed into a flame, turned into droplets, and then cooled and solidified. After cooling and solidification, the alumina powder can be obtained by collecting the cooled and solidified material using a cyclone or a bag filter. More specifically, the electrofused alumina pulverized material is melted while being sprayed into the flame from the top of the furnace, water is sprayed into the furnace from the middle body of the furnace body to perform quenching, and the obtained spheroidized material is transported together with the exhaust gas to a bag filter by a blower and collected. The flame is formed by spraying fuel gas such as hydrogen, natural gas, acetylene gas, propane gas, butane, and combustion supporting gas such as air and oxygen from a combustion burner set in the furnace body. The flame temperature is preferably 2100°C or higher, and particularly preferably 2100 to 2300°C.

[0064] Alumina powder having a spherical shape can also be obtained by granulating a precursor powder obtained by using a spray dryer such as a spray dryer to prepare a slurry of raw material powder or an aqueous solution in which aluminum ions are dissolved, and then feeding the granulated precursor powder into a firing furnace such as an electric furnace or a gas furnace, and firing the granulated precursor powder at 1300° C. or higher for 2 to 12 hours. The alumina powder used in the resin composition of the present embodiment is preferably produced by a flame fusion method, since the particle size distribution can be adjusted and the enlargement caused by sintering of particles can be reduced.

[0065] The alpha crystallization rate of the alumina powder can be controlled by changing the cooling conditions after the heat treatment of the fused alumina pulverized material. Cooling can be performed by spraying water into the furnace from the center body of the furnace. The cooling conditions inside the furnace can be adjusted by the amount of water sprayed. For example, the amount of water sprayed for cooling can be 100 L (liters) or more per hour.

[0066] The average particle diameter D50 of the alumina powder used in the resin composition of the present embodiment, as measured by a laser analysis scattering method, can be, for example, 15 to 25 μm. The average particle diameter can be adjusted by controlling the average particle diameter of the raw material powder.

[0067] The alumina powder contains sodium (Na + ) and chlorine (Cl - The amount of ionic impurities such as ZnO, ZnS, etc. is preferably 300 ppm or less, more preferably 100 ppm or less, and particularly preferably 20 ppm or less, calculated as Na.

[0068] In order to reduce the amount of ionic impurities to 300 ppm or less, washing with water or an acidic aqueous solution such as hydrochloric acid or sulfuric acid may be performed. Washing can be performed, for example, by repeating the steps of reslurrying the alumina powder, dehydrating it using a dehydrator such as a filter press, a centrifugal filter, or a screw decanter, and then reslurrying it.

[0069] The alumina powder can be obtained by drying the resulting dehydrated cake with a tray dryer or paddle dryer, or by drying the slurry after washing with a spray dryer or vibrating fluidized dryer, etc. The drying temperature is not particularly limited, but is usually 120°C or higher and 300°C or lower.

[0070] The alumina powder thus obtained is blended in the resin composition of this embodiment in an amount of 80 to 90% by mass based on the entire resin composition. Although the resin composition of this embodiment contains a high loading amount of alumina powder exceeding 80% by mass based on the entire resin composition, the increase in viscosity is suppressed and the resin composition has high thermal conductivity. In addition, since the resin composition of this embodiment contains alumina powder with a reduced amount of ionic impurities as described above, the amount of ionic impurities contained in the resin composition itself can be 0.002% by mass or less based on the entire resin composition. By making the amount of chlorine as an ionic impurity the above value or less, wire corrosion and deterioration of moisture resistance reliability caused by ionic impurities can be prevented.

[0071] When the resin composition of the present embodiment contains a plurality of types of inorganic fillers, the total amount of the inorganic fillers is used in the above range.

[0072] The resin composition of the present embodiment may contain the following components in addition to those described above. [Hardening agent (C)] The resin composition may contain a curing agent (C). The curing agent (C) is not particularly limited as long as it reacts with the thermosetting resin (A) to cure it, but examples of the curing agent include linear aliphatic diamines having 2 to 20 carbon atoms, such as ethylenediamine, trimethylenediamine, tetramethylenediamine, and hexamethylenediamine, as well as amines such as metaphenylenediamine, paraphenylenediamine, paraxylenediamine, 4,4'-diaminodiphenylmethane, 4,4'-diaminodiphenylpropane, 4,4'-diaminodiphenylether, 4,4'-diaminodiphenylsulfone, 4,4'-diaminodicyclohexane, bis(4-aminophenyl)phenylmethane, 1,5-diaminonaphthalene, metaxylenediamine, paraxylenediamine, 1,1-bis(4-aminophenyl)cyclohexane, and dicyanodiamide; resole-type phenolic resins, such as aniline-modified resole resins and dimethyl ether resole resins; phenol novolac resins (PN), chlorinated polystyrene resins, and the like. Examples of the phenolic resin include novolac-type phenolic resins such as resol novolac resins, tert-butylphenol novolac resins, and nonylphenol novolac resins; phenolic aralkyl resins such as phenylene skeleton-containing phenolic aralkyl resins and biphenylene skeleton-containing phenolic aralkyl resins; phenolic resins having a condensed polycyclic structure such as a naphthalene skeleton or an anthracene skeleton; polyoxystyrenes such as polyparaoxystyrene; alicyclic acid anhydrides such as hexahydrophthalic anhydride (HHPA) and methyltetrahydrophthalic anhydride (MTHPA), and aromatic acid anhydrides such as trimellitic anhydride (TMA), pyromellitic anhydride (PMDA), and benzophenonetetracarboxylic acid (BTDA); polymercaptan compounds such as polysulfides, thioesters, and thioethers; isocyanate compounds such as isocyanate prepolymers and blocked isocyanates; and organic acids such as carboxylic acid-containing polyester resins. These may be used alone or in combination of two or more.Among these, it is preferable to use phenol novolac type resin (PN), triphenolmethane type phenol resin (MF), biphenyl skeleton-containing polyfunctional phenol resin (polyvalent MAR), and binaphthalene type phenol resin (naphthalene resin), which exhibit high Tg, since their reliability is not impaired even when the semiconductor chip is exposed to high temperatures.

[0073] The content of the curing agent (C) in the resin composition is not particularly limited, but is preferably, for example, from 1 mass % to 12 mass % and more preferably from 3 mass % to 10 mass % relative to the entire resin composition. By setting the content of the curing agent (C) to be equal to or more than the above lower limit, the resin composition is easily cured appropriately. On the other hand, by setting the content of the curing agent (C) to be equal to or less than the above upper limit, appropriate fluidity is maintained, and low-temperature / low-pressure sealing is easily achieved.

[0074] [Cure accelerator (D)] The resin composition may contain a curing accelerator (D). The curing accelerator (D) has high activity. This allows low-temperature curing to be achieved, but if used as is without any special measures, the reaction will proceed during storage, reducing the shelf life. Examples of the curing accelerator (D) include phosphorus atom-containing compounds such as organic phosphines, tetra-substituted phosphonium compounds, phosphobetaine compounds, adducts of phosphine compounds and quinone compounds, or adducts of phosphonium compounds and silane compounds; amidine compounds such as 1,8-diazabicyclo(5,4,0)undecene-7 and imidazole; and nitrogen atom-containing compounds such as tertiary amines such as benzyldimethylamine, amidinium salts, or ammonium salts. Among them, the curing accelerator (D) is preferably an imidazole-based curing accelerator or a phosphorus-based curing accelerator. As the imidazole-based curing accelerator, it is more preferable to include, for example, an imidazole compound of an amidine-based compound. Examples of the imidazole compound include, but are not limited to, 2-methylimidazole, 2-phenylimidazole, imidazole-2-carbaldehyde, 5-azabenzimidazole, and 4-azabenzimidazole. Among them, 2-methylimidazole is preferably used.

[0075] The content of the curing accelerator (D) in the resin composition is not particularly limited, but is preferably, for example, from 0.1 mass % to 5 mass % and more preferably from 0.2 mass % to 4 mass % relative to the entire resin composition. By setting the content of the curing accelerator (D) to the above lower limit or more, the resin composition can be appropriately cured. On the other hand, by setting the content of the curing accelerator (D) to the above upper limit or less, the molten state can be prolonged, and the low viscosity state can be prolonged, which makes it easier to realize low-temperature sealing.

[0076] [Coupling agent (E)] The resin composition may contain a coupling agent (E). As the coupling agent (E), known coupling agents such as various silane-based compounds such as epoxysilane, mercaptosilane, aminosilane, alkylsilane, ureidosilane, and vinylsilane, titanium-based compounds, aluminum chelates, and aluminum / zirconium-based compounds can be used. More specifically, vinyltrichlorosilane, vinyltrimethoxysilane, vinyltriethoxysilane, vinyltris(β-methoxyethoxy)silane, γ-methacryloxypropyltrimethoxysilane, β-(3,4-epoxycyclohexyl)ethyltrimethoxysilane, γ-glycidoxypropyltrimethoxysilane, γ-glycidoxypropyltriethoxysilane, γ-glycidoxypropylmethyldimethoxysilane, γ-methacryloxypropylmethyldiethoxysilane, γ-methacryloxypropyltriethoxysilane, vinyltriacetoxysilane, γ-mercaptopropyltrimethoxysilane, γ-aminopropyltriethoxysilane, γ-anilinopropyltrimethoxysilane, γ-anilinopropylmethyldimethoxysilane, γ-[bis(β-hydroxyethyl)]aminopropyltriethoxysilane, N-β-(aminoethyl)-γ-aminopropyltrimethoxysilane, N-β-(aminoethyl) - silane coupling agents such as gamma-aminopropyltriethoxysilane, N-beta-(aminoethyl)-gamma-aminopropylmethyldimethoxysilane, N-phenyl-gamma-aminopropyltrimethoxysilane, gamma-(beta-aminoethyl)aminopropyldimethoxymethylsilane, N-(trimethoxysilylpropyl)ethylenediamine, N-(dimethoxymethylsilylisopropyl)ethylenediamine, methyltrimethoxysilane, dimethyldimethoxysilane, methyltriethoxysilane, N-beta-(N-vinylbenzylaminoethyl)-gamma-aminopropyltrimethoxysilane, gamma-chloropropyltrimethoxysilane, hexamethyldisilane, vinyltrimethoxysilane, gamma-mercaptopropylmethyldimethoxysilane, 3-isocyanatopropyltriethoxysilane, 3-acryloxypropyltrimethoxysilane, and hydrolyzate of 3-triethoxysilyl-N-(1,3-dimethyl-butylidene)propylamine;Examples of titanate-based coupling agents include isopropyl triisostearoyl titanate, isopropyl tris(dioctyl pyrophosphate) titanate, isopropyl tri(N-aminoethyl-aminoethyl) titanate, tetraoctyl bis(ditridecyl phosphite) titanate, tetra(2,2-diallyloxymethyl-1-butyl)bis(ditridecyl)phosphite titanate, bis(dioctyl pyrophosphate)oxyacetate titanate, bis(dioctyl pyrophosphate)ethylene titanate, isopropyl trioctanoyl titanate, isopropyl dimethacryl isostearoyl titanate, isopropyl tridodecylbenzenesulfonyl titanate, isopropyl isostearoyl diacryl titanate, isopropyl tri(dioctyl phosphate) titanate, isopropyl tricumyl phenyl titanate, and tetraisopropyl bis(dioctyl phosphite) titanate. These may be used alone or in combination of two or more.

[0077] The content of the coupling agent (E) in the resin composition is not particularly limited, but is preferably 0.05% by mass or more and 3% by mass or less, and more preferably 0.1% by mass or more and 2% by mass or less, based on the entire resin composition. By making the content of the coupling agent (E) equal to or more than the lower limit, the dispersion of the inorganic filler (B) in the resin composition can be improved. In addition, by making the content of the coupling agent (E) equal to or less than the upper limit, the flowability of the resin composition can be improved, and the moldability can be improved.

[0078] Furthermore, in addition to the above components, the resin composition of the present embodiment may contain various additives, such as colorants such as carbon black; release agents such as natural waxes, synthetic waxes, higher fatty acids or metal salts thereof, paraffin, and polyethylene oxide; ion scavengers such as hydrotalcite; stress reduction agents such as silicone oil and silicone rubber; flame retardants such as aluminum hydroxide; and antioxidants.

[0079] Although the embodiments of the present invention have been described above, these are merely examples of the present invention, and various configurations other than those described above can also be adopted. Examples of embodiments are given below. 1. A metal circuit board; a power semiconductor element provided on one surface of the metal circuit board; a bonding layer made of a sintering paste that bonds the power semiconductor element and the metal circuit board; a heat dissipation sheet laminated on a surface of the metal circuit board opposite to a surface on which the power semiconductor element is provided, A resin composition used to seal the power semiconductor element, the bonding layer, the circuit board, and the heat dissipation sheet, The resin composition includes an epoxy resin and an inorganic filler, The glass transition temperature of the resin composition is 170° C. or higher and 300° C. or lower, A resin composition, wherein a cured product of the resin composition has an average linear expansion coefficient α1 of 5 ppm / K or more and 15 ppm / K or less at a temperature below the glass transition temperature, and an average linear expansion coefficient α2 of 25 ppm / K or more and 65 ppm / K or less at a temperature above the glass transition temperature. 2. The resin composition according to 1, wherein the inorganic filler is contained in an amount of 80% by mass or more and 90% by mass or less based on the total solid content of the resin composition. 3. The resin composition according to 1 or 2, wherein the inorganic filler comprises silica powder. 4. The resin composition according to any one of 1. to 3., further comprising a phenol-based curing agent. 5. The resin composition according to any one of 1. to 4., further comprising a curing accelerator. 6. A metal circuit board; a power semiconductor element provided on one surface of the metal circuit board; a bonding layer made of a sintering paste that bonds the power semiconductor element and the metal circuit board; a heat dissipation sheet laminated on a surface of the metal circuit board opposite to a surface on which the power semiconductor element is provided, a sealing material that covers the power semiconductor element, the bonding layer, the circuit board, and the heat dissipation sheet, The sealing material is made of a cured product of the resin composition according to any one of 1. to 5. Power module. EXAMPLES

[0080] The present invention will be described below with reference to examples and comparative examples, but the present invention is not limited to these.

[0081] (Examples 1-2, Comparative Examples 1-2) <Preparation of Encapsulating Resin Composition> For each of the Examples and Comparative Examples, an encapsulating resin composition was prepared as follows. First, the raw materials formulated according to Table 1 were mixed at room temperature using a mixer, and then roll-kneaded at 90 to 120° C. The resulting kneaded product was then cooled and pulverized to obtain a resin composition. Details of each raw material component in Table 1 are as follows.

[0082] (Epoxy resin) Epoxy resin 1: a biphenyl skeleton-containing multifunctional epoxy resin represented by formula (13A) of International Publication No. 2013 / 136685 (manufactured by Meiwa Kasei Co., Ltd.) Epoxy resin 2: Tris(hydroxyphenyl)methane type epoxy resin (Mitsubishi Chemical Corporation, jER 1032H60) Epoxy resin 3: Phenol aralkyl type epoxy resin containing biphenylene skeleton (manufactured by Nippon Kayaku Co., Ltd., NC3000) (hardening agent) Curing agent 1: Phenol-resorcinol-4,4'-bischloromethylbiphenyl polycondensate (a polyfunctional biphenyl aralkyl-type phenolic resin represented by formula (12A) in WO 2013 / 136685) (manufactured by Meiwa Kasei Co., Ltd.) Hardener 2: Trisphenylmethane type phenol novolac resin (MEH-7500, manufactured by Meiwa Kasei Co., Ltd.) Hardener 3: Biphenyl aralkyl type phenolic resin (manufactured by Nippon Kayaku Co., Ltd., KAYAHARD GPH-65) (Inorganic filler) Inorganic filler 1: Fused spherical silica (Denka, FB-560) Inorganic filler 2: Spherical silica (Admatechs Co., Ltd., SO-25R) (Cure accelerator) Curing accelerator 1: Tetraphenylphosphonium-4,4'-sulfonyldiphenolate (Sumitomo Bakelite Co., Ltd.) (Coupling Agent) Coupling agent 1: 3-glycidoxypropyltrimethoxysilane (JNC, S510) (Release agent) Release agent 1: Glycerol trimontanate ester (Clariant Japan, Ricorb-WE-4) (Coloring agent) Colorant 1: Carbon black (Mitsubishi Chemical, MA-600)

[0083] <Evaluation of physical properties of encapsulating resin composition> The encapsulating resin composition obtained above was measured for the following physical properties. The measurement results are shown in Table 1 below. (Fluidity (Spiral Flow)) Using a low pressure transfer molding machine (KOTAKISEIKI CO., LTD., "KTS-30"), the obtained encapsulating resin composition was injected into a metal mold for measuring spiral flow conforming to EMMI-1-66 under the conditions of a metal mold temperature of 175°C, an injection pressure of 6.9 MPa, and a pressure retention time of 120 seconds, and the composition was cured to measure the spiral flow. The unit is cm.

[0084] (glass transition temperature) The obtained encapsulating resin composition was injected and molded using a transfer molding machine at a mold temperature of 175°C, injection pressure of 9.8MPa, and curing time of 120 seconds to obtain a molded product of 15mm x 4mm x 4mm. The obtained molded product was then post-cured at 175°C for 4 hours to prepare a test piece. Thereafter, the obtained test piece was subjected to thermomechanical analysis using a thermomechanical analyzer (Seiko Instruments Inc., TMA100) under conditions of a measurement temperature range of 0°C to 400°C and a heating rate of 5°C / min to measure the glass transition temperature. The unit of glass transition temperature is °C.

[0085] (Linear expansion coefficient of cured product of encapsulating resin composition) The above TMA measurement data was analyzed to determine the average linear expansion coefficient. Glass transition temperature End 300℃ or less Range The average linear expansion coefficient at α 2 α 2 The unit is [ppm / K]. 20℃ End Glass transition temperature Within the range of The average linear expansion coefficient of α 1 α 1 The unit is [ppm / K].

[0086] <Power module performance evaluation> A molded body made of the thermally conductive composition described in Example 1 of WO 2017-006854 was used as a sintering layer, a thermally conductive sheet described in Example 1 of WO 2016-002892 was used as a heat dissipation sheet, and sealing was performed with the sealing resin composition of each Example and Comparative Example to produce the power module shown in Figure 1. The molding conditions for the sealing resin composition were 175°C for 2 minutes, and the after-cure conditions were 175°C for 4 hours.

[0087] The obtained power module was evaluated for the following performance. (HTRB test: Evaluation of HTRB resistance) The power module obtained in each example was subjected to a treatment for 1000 hours in an HTRB tester at 150° C. and a voltage of 1200 V. The withstand voltage was measured before and after the treatment and evaluated according to the following criteria. ○: The decrease in withstand voltage after treatment compared to before treatment is less than 5% ×: The decrease in withstand voltage after treatment compared to the withstand voltage before treatment is 5% or more.

[0088] (TC peeling) The power modules obtained in each example were subjected to 1000 tests using a simple package for TC evaluation under conditions of -65°C / 30 minutes to 150°C / 30 minutes. The presence or absence of peeling in the semiconductor element during the TC test was observed using SAT and evaluated according to the following criteria (number of packages for each n=10). ○: The number of packages that experienced peeling after TC testing was less than one ×: Peeling occurred in one or more packages after TC test

[0089] [Table 1]

[0090] The power module produced using the encapsulating resin composition of the example had excellent HTRB resistance, and no peeling occurred in the TC test, showing excellent reliability. [Explanation of symbols]

[0091] 1. Power semiconductor chip 2 Sintering layer 3 Cu circuit (metal circuit board) 4. Heat dissipation sheet 5 Cu base plate (heat dissipation material) 6. Encapsulating materials 7 Lead Frame 10 Power Module

Claims

1. A metal circuit board; a power semiconductor element provided on one surface of the metal circuit board; a bonding layer made of a sintering paste that bonds the power semiconductor element and the metal circuit board; a heat dissipation sheet laminated on a surface of the metal circuit board opposite to a surface on which the power semiconductor element is provided, A resin composition used to seal the power semiconductor element, the bonding layer, the circuit board, and the heat dissipation sheet, The resin composition includes an epoxy resin and an inorganic filler, the epoxy resin is a biphenyl skeleton-containing polyfunctional epoxy resin or a tris(hydroxyphenyl)methane type epoxy resin having an epoxy equivalent of 90 to 300; The inorganic filler is present in an amount of 82% by mass or more and 90% by mass or less based on the total solid content of the resin composition, The glass transition temperature of the resin composition is 170° C. or higher and 300° C. or lower, A resin composition, wherein a cured product of the resin composition has an average linear expansion coefficient α1 at a temperature below the glass transition temperature of 5 ppm / K or more and 15 ppm / K or less, and an average linear expansion coefficient α2 at a temperature equal to or more than the glass transition temperature of 25 ppm / K or more and 65 ppm / K or less.

2. The resin composition according to claim 1 , wherein the inorganic filler comprises a silica powder.

3. The resin composition according to claim 1 or 2, further comprising a phenol-based curing agent.

4. The resin composition according to claim 1 , further comprising a curing accelerator.

5. A metal circuit board; a power semiconductor element provided on one surface of the metal circuit board; a bonding layer made of a sintering paste that bonds the power semiconductor element and the metal circuit board; a heat dissipation sheet laminated on a surface of the metal circuit board opposite to a surface on which the power semiconductor element is provided, a sealing material that covers the power semiconductor element, the bonding layer, the circuit board, and the heat dissipation sheet, The sealing material is made of a cured product of the resin composition according to any one of claims 1 to 4. Power module.

Citation Information

Patent Citations

  • Semiconductor power module

    JP2006179732A

  • Package mounting body

    JP2019062122A

  • Resin composition for encapsulation and power module

    JP2019151691A

  • Power module

    JP2022021143A

  • Semiconductor device, power module, method for manufacturing semiconductor device and method for manufacturing power module

    WO2017138402A1